Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

Techno-economic performance of an advanced process for synergistic removal of NO/SO2/CO2 via H2O2 pre-oxidation coupled with ammonia scrubbing - Jiaxing Du; Qingqing Liang; Yifan Wang; Hui Xu; Linlin Xu; Yan Liang; Guangying Wang; Lei Bei; Chuanwei Li; Zewei Zhang; Lushi Sun (Fuel, 2027)

Role of intraseasonal and interannual processes in ocean heat content anomalies east of Mindanao - Zhen Li; Linlin Zhang; Mengmeng Li; Weiqi Song; Xiaoluan Yan; Tangdong Qu (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Heterogeneous reaction of NO2 with hydroxyapatite particles: Effects on phosphorus water solubility - Linlin Ye; Yan Huang; Linfeng Zhang; Panya Xu; Jingjing Wang; Chengzhu Zhu; Tong Zhu; Mingjin Wang (Atmospheric Environment, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Unique coordination of four-metal-atom clusters on C5N2H2 boosts nitrogen reduction reaction performance: a DFT study - Linlin Li; Shaopeng Xu; Yan Yan; Mengmeng Wang; Yan Chen; Jiaojiao Chen; Wei Li; Xunlei Ding (Fuel, 2026)

Porous solar evaporator with hierarchical photothermal structure for highly-performance desalination and water remediation - Yuqian He; Chunguang Liu; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Xi Quan Cheng (Chemical Engineering Journal, 2026)

Synergistic enhancement of heavy rare earth elements leaching from ion-adsorption rare earth ores using fungal metabolites supplemented with ammonium sulfate - Yun Fang; Hailan Wang; Linlin Yan; Jianxiong Zeng; Siqi Chen; Jun Liu; Guowei Wang; Yang Liu; Jun Wang; Chunqiao Xiao (Hydrometallurgy, 2026)

2-Methoxyestradiol Suppresses Stemness and Epithelial-Mesenchymal Transition in Drug-Resistant Esophageal Squamous Cell Carcinoma by Targeting the Snail Signaling Pathway in Cancer Stem Cells - Jie Yan; Shuhua Han; Keqi Zhang; Linlin Li; Mingjing He; Haoqing Cao; Meiru Zhu; Bingjie Bi; Qiang Xu; Cong Wang (Stem Cell Reviews and Reports, 2026)

Genesis of Successive Quasi-Linear Convective Systems over North China: Dynamical and Thermodynamic Forcing by a Cold Vortex, Complex Terrain, and Surface Boundaries - Yan Zhang; Rudi Xia; Jinfang Yin; Jianhua Sun; Linlin Zheng (Journal of Meteorological Research, 2026)

Performance and wastewater treatment efficiency of artificially prepared aerobic granular sludge - Xuanzhe Yan; Jinlong Wang; Kailong Liu; Hao Wu; Wei He; Yongmei Zhang; Linlin Tong; Su Li; Zhaoyang You (Biodegradation, 2026)

5-FU chemotherapy induces functional CD7+ and IL7R+ CTLs infiltration to suppress colorectal tumor progression - Yanmin Wu; Yan Li; Xufeng Yao; Yiyang Pan; Linlin Chen; Jian Zhang; Boyu Luo; Yue Teng; Mingqing Zhang; Chunwan Lu (Science China Life Sciences, 2026)

Prescription principle, phytochemistry, pharmacological activities and clinical applications of Huangqin decoction: a comprehensive review - Yan Fang; Haizhen Liang; Linlin Lu; Xijie Tian; Yuting Zhang; Junyu Zhang; Zhifeng Dai; Xiaojuan Chen; Juan Song; Tao Su; Zhongqiu Liu; Baiping Ma (Phytochemistry Reviews, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Characterizing functional connectivity gradients for the hippocampus–amygdala complex in healthy and psychiatric cohorts - Xiang-Shen Liu; Janna N. Vrijsen; Linlin Yan; Koen V. Haak; Rose M. Collard; Philip F. P. van Eijndhoven; Christian F. Beckmann; Guillén Fernández; Indira Tendolkar; Nils Kohn (Brain Structure and Function, 2026)
The hippocampus and amygdala play essential roles in human cognition and emotion, through their extensive connectivity with other brain regions and close interaction between them. Uncovering the functional organization of the hippocampus–amygdala complex and its relationship with neurotransmitter distribution can enhance our understanding of their biological functionality, and provide a basis for further exploration of the clinical relevance. An emerging functional connectivity analysis method termed connectopic mapping, may offer a novel approach to characterize this functional organization. In this study, we applied connectopic mapping to the hippocampus-amygdala complex, testing its utility with resting-state functional magnetic resonance imaging (fMRI) scans of two independent datasets: one comprising healthy individuals ( N = 410) and another comprising a psychiatric cohort ( N = 367). The spatial organization of derived gradient maps was compared to 18 positron emission tomography (PET) or single photon emission computed tomography (SPECT) scan templates for different neurotransmitter systems. Individual gradient–neurotransmitter similarity indices were correlated with mental health outcomes. Our analyses identified six distinct gradient maps in both datasets. The third-order gradients showed stable similarity with 5-HT1A receptor maps across various resting-state scans. Similarities were also observed between gradient maps and the distribution patterns of neurotransmitters within the dopaminergic system. Individual gradient-to-5-HT1A similarity was positively correlated with depressive severity and anxiety sensitivity, highlighting the psychopathological relevance. These findings demonstrate that across the psychiatric continuum, connectopic mapping is a powerful tool for exploring the relationship between functional connectivity organization and neurotransmitter distribution, showing potential as a comprehensive transdiagnostic biomarker.

Bioaugmentation of thiourea-acclimated biomass relieves thiourea’s inhibition of nitrification - Meng Huang; Xiaobing Gao; Ning Yan; Fei Liu; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Environmental Chemical Engineering, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Cyclic performance of dual stage energy dissipation joints for connecting CFST column and exterior wide-flat beam - Mingyang Wei; Linlin Song; Jianhua Zhang; Cheav Por Chea; Yan Geng; Xueming Zhang; Dianwei Gao; Zhicheng Liu (Engineering Structures, 2026)

Mediating Effect of Self-Efficacy Between Self-Perceived Burden and End-of-Life Communication Difficulties in Cancer Patients - Yalin Zhu; Linlin Shi; Yuanyuan Jiang; Yuyan Fan; Huixian Zhang; Shouxia Chai; Yan Li (Journal of Cancer Education, 2026)

Hominin occupation of the Western Qinling Mountains as early as ∼900 ka - Zaijun Li; Jian Wang; Chongwen Luo; Yongbo Quan; Linlin Yan; Yuanxin Li; Linxueyi Wang; Shengli Yang; Jia Jia; Ziwei Tao; Tingjiang Peng; Zhenzhong Tian; et al. (Science Bulletin, 2026)

Occurrence, composition profiles, and human exposure assessment of liquid crystal monomers in indoor dust from Wuxi, China - Yiyang Yao; Linlin Wu; Run Zhou; Xi Wang; Yan Gong; Rong Chen; Wenwei Liu (Environmental Pollution, 2026)

Cadmium exposure is associated with impaired ovarian function: Potential role of cadmium-induced ferroptosis in granulosa cells - Jing Li; Yutong Wang; Yali Huang; Nidong Li; Yingxin Zhu; Shengli Lin; Linlin Wang; Wei Guo; Lailai Yan; Chan Tian; Ying Wang (Journal of Hazardous Materials, 2026)

O2-supplementing photosensitizer AuNCs@TAT as a highly efficient NIR-II-controllable pyroptosis inducer for cancer photoimmunotherapy - Linlin Xie; Xingye Ma; Zheng Wang; Caifang Wang; Zhongxin Xiao; Ling-Dong Sun; Chun-Hua Yan; Chen-Jie Fang (Chemical Engineering Journal, 2026)

Drug screening reveals the mechanism of toyocamycin-induced apoptosis in triple-negative breast cancer organoids - Houshi Ma; Linlin Lu; Yuqing Tu; Xiaoran Chang; Huabin Jiang; Tianhang Yang; Shun Wang; Jinxian Wang; Jinbing Xue; Yan Chen; Gangyin Luo (Toxicology and Applied Pharmacology, 2026)

Synergistic DFT and experimental design of Ga/W Co-Doped SnS2 microspheres with enriched sulfur vacancies for enhanced NO2 sensing - Wei Zhao; Lanlan Guo; Xin Shi; Linlin Dong; Yingli Yang; Xueli Yang; Xiaolian Liu; Guodong Wang; Yan Wang (Chemical Engineering Journal, 2026)

Preparation and application of ceramic membranes incorporating graphite tailings for oil wastewater treatment - Lixin Li; Pengyu Yan; Linlin Huang; Zhaoshun Zhan; Jun Zhang; Xinyu Li; Wei Chai; Qingju Tang; Zhurui Shen (Chemical Engineering Journal, 2026)

Apple diameter prediction during mechanical picking based on flexible force-sensing and CNN-BiLSTM-Attention method - Mingyang Lu; Linlin Sun; Haidi Chu; Mochen Liu; Jing Wang; Hongjian Zhang; Zhanhua Song; Yao Lu; Jinxing Wang; Yinfa Yan (Computers and Electronics in Agriculture, 2025)

Research hotspots and trends in Spartina alterniflora studies (1970–2023): A bibliometric analysis - Dandan Yan; Shanshan Wang; Peng Song; Yuqing Zhang; Yiming Huang; Yu Wang; Wenyan Zhu; Linlin Wu (Marine Pollution Bulletin, 2025)

Impacts of climate change and land use changes on heat island effect in the Guangdong-Hong Kong-Macao Greater Bay Area under the SSP-RCP framework - Xin Yan; Alex Hay-Man Ng; Xun Liu; Qianqian Zhou; Linlin Ge (Sustainable Cities and Society, 2025)

Alginate-polylysine-alginate (APA) microencapsulated transgenic human amniotic epithelial cells ameliorate fibrosis in hypertrophic scars - Linlin Su; Yanhui Jia; Yan Li; Jihong Shi (Inflammation Research, 2025)

Chemical composition and mixing states of individual atmospheric particles in summer and winter: a micro-Raman spectroscopy study - Yan Huang; Qingcheng Li; Linlin Ye; Jingjing Wang; Yidan Zhang; Tong Zhu; Chengzhu Zhu; Mingjin Wang (Atmospheric Environment, 2025)

MitoQ reducing sevoflurane-induced cognitive dysfunction by modulating mitochondrial dysfunction - Hengjie Su; Zhibin He; Haotian Wu; Linlin Wang; Huan Zhang; Siyi Yan (Metabolic Brain Disease, 2025)

Superhydrophilic adsorptive nanofiber membranes for ultrafast and highly-efficient waterborne nanoplastic removal - Jingwen Zhou; Mi Zhou; Longjun Wang; Jiayu Tong; Xinhao Li; Jingru Zhou; Yuqian He; Linlin Yan; Xiquan Cheng (Journal of Hazardous Materials, 2025)

Rb-Sr dating of pyrite, Zircon U-Pb geochronology, and Sr-Nd-Hf isotopic geochemistry of the Baiyun Au deposit in the Qingchengzi Orefield, Liaodong Peninsula, Northeast China - Peng Zhang; Junchao Lü; Yan Zhao; Linlin Kou; Wei Pang (Journal of Geochemical Exploration, 2025)

Double synergistic strategy: mechanism of acetone sensing performance enhancement by Pt@Cu3(HHTP)2 derivatives modifying three-dimensional inverse opal In2O3 - Lanlan Guo; Jiaru Yang; Yuying Cai; Linlin Dong; Yingli Yang; Xueli Yang; Xiaolian Liu; Guodong Wang; Yan Wang (Chemical Engineering Journal, 2025)

Assessing Intra-Annual Spatial Distribution of Amphioctopus fangsiao in the East China Sea and Southern Yellow Sea Using Ensemble Models - Yan Cui; Xiaodi Gao; Shaobo Yang; Shengfa Li; Linlin Yang (Journal of Marine Science and Engineering, 2025)
Understanding the distribution pattern and its drivers of species is crucial for developing effective and sustainable management strategies. Amphioctopus fangsiao is the octopus of significant commercial and ecological value along the coast of China, with multiple distinct populations. However, research on their ecological dynamics remains limited and requires further investigation. Here, ensemble models were constructed to examine the spatio-temporal distribution and inter-populational differentiation in environmental adaptability of A. fangsiao in the East China Sea (ECS) and the South Yellow Sea (SYS). Specifically, we generated the ensemble models by integrating Gradient Boosting Machine (GBM), Generalized Linear Models (GLMs), and Maximum Entropy Models (MaxEnt) for the different populations across four seasons, using fishery-independent data collected from 2015 to 2021. The results revealed two hotspots of A. fangsiao in the ECS and SYS: one is the area of SYS along the coastal waters, with latitudes 33° N–34° N and longitudes 120° E–122° E (northern population, NP); the other one is near the Kuroshio-adjacent area with latitudes 28.5° N–29° N and longitudes 123° E–124.5° E (southern population, SP). Both NP and SP exhibited distinct seasonal habitat preferences, with key environmental drivers showing seasonal variations. The NP tended to inhabit coastal waters with lower sea surface heights (SSHs), shallower water depth, and a narrower sea bottom salinity range (SBS). In contrast, SP preferred marine environments with a thicker mixed layer thickness (MLT) and higher concentrations of bottom chlorophyll-a (Chl_b). The environmental characterization of suitable habitats revealed distinct patterns in resource utilization and environmental adaptation strategies between the two populations. This study provides fundamental data for understanding A. fangsiao population dynamics and underscores the importance of considering population-specific habitat preferences within dynamic marine environments.

Non-destructive prediction of soluble solids content and firmness and maturity determination of guava fruit using color and fluorescence imaging - Shaozhen Lin; Kangting Yan; Zhilei Sun; Zhijie Zhang; Yubin Lan; Linlin Wang; Yali Zhang (Postharvest Biology and Technology, 2025)

Thermodynamic drivers of rice glutenin Assembly: Multiscale analysis of Hierarchical structure and intermolecular bonding - Wanshan Yang; Huining Zhang; Haoyu Li; Yuhan Jiang; Zhiqi Wang; Menglu Yang; Sitong Liu; Yinyuan He; Bing Wang; Linlin Liu; Yan Wang; Fenglian Chen; et al. (Journal of Cereal Science, 2025)

Effects of Land-Use Change on Soil Infiltrability and Preferential Flow in Typical Low Hilly Area - Linlin Chu; Rong Ma; Yue Liu; Yan Zhao; Lidong Bi; Chen Dan (Journal of Soil Science and Plant Nutrition, 2025)

Norgestrel shows androgenic properties and triggers reproductive neuroendocrine toxicity in the testes of Pacific oysters (Crassostrea gigas) - Yan Fang; Baojun Liu; Juan Wang; Haoyang Zhong; Linlin Fan; Yuchao Huang; Changkun Chen; Songtao Lu; Tao Zheng (Journal of Hazardous Materials, 2025)

Seasonal distribution patterns of P-cycling-related microbes and its association with internal phosphorus release in the eutrophic Lake Chaohu, China - Tingting Sun; Linlin Zhu; Tao Huang; Pengliang Tao; Yan Bao; Bo Wang; Qingye Sun; Kaining Chen (Journal of Environmental Sciences, 2025)

Mutual influence of bubble evolution and seepage flow in heterogeneous porous matrices - Linlin Gu; Shicai Sun; Rundong Zhang; Rongtao Yan; Yonghao Yin; Guanru Gong (Gas Science and Engineering, 2025)

circ_0000554 promotes macrophage M2 polarization mediated by glycolytic reprogramming and aggravates COPD injury - Yamei Song; SiQin Han; Linlin Liu; Lifeng Zheng; Jing Wang; Zhaobo Cui; Xixin Yan (Toxicology Letters, 2025)

Social and ecological factors on the perception of cultural ecosystem services and disservices: Insights from Shanghai, China - Rongfei Su; Shiyu Ye; Linlin Yu; Jingbin Wu; Yan Kang; Ruishan Chen (Landscape and Urban Planning, 2025)

Impacts of spatial resolutions of UAV-LiDAR-derived DEMs on erosion modelling in the hilly and gully Loess Plateau - Wenli Li; Pengfei Li; Lu Yan; Jinfei Hu; Leiqin Wang; Dou Li; Yang Dan; Linlin Huang; Guangju Zhao (CATENA, 2025)

Construction of Fenton-like systems based on hierarchical nanoconfinement for efficient antibiotic removal - Linlin Su; Wei Hu; Xiaolun He; Chao Chen; Min Xu; Xiaoyu Yu; Yan Liu; Gang Yang; Lulu Long (Journal of Environmental Chemical Engineering, 2025)

Spatiotemporal variations of dissolved nitrous oxide concentrations in small water bodies in a typical urban landscape in eastern China - Xuebing Chen; Yuye Shen; Yihong Liu; Fangfang Zhang; Linlin Tian; Jing Wang; Yanjiang Cai; Yan Li; Scott X. Chang (Environmental Pollution, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Seasonal and spatial distribution of AmphiOctopus fangsiao and Octopus variabilis in the southern Yellow and East China Seas: Fisheries management implications based on climate scenario predictions - Linlin Yang; Min Xu; Zunlei Liu; Yi Zhang; Yan Cui; Shengfa Li (Regional Studies in Marine Science, 2025)

Convert iron tailings waste into a novel Mg-Fe-Al hybrid magnetic coagulant for enhanced pretreatment of swine wastewater - Linlin Hao; Jingshuang Yan; Jiaoying Guo; Nannan Wang; Ming Zeng (Journal of Environmental Chemical Engineering, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

Seasonal spatial distribution patterns of AmphiOctopus ovulum in the East China Sea: current status future projections under various climate change scenarios - Linlin Yang; Min Xu; Yan Cui; Shuhao Liu (Frontiers in Marine Science, 2025)
Currently, there is also little up to date information on the the current population status and life history traits of AmphiOctopus ovulum , a very often seen cephalopod species in the East China Sea. It is therefore important to figure out the seasonal spatial distribution of this species, both in terms of number and biomass, and the environmental variables which determine them. Additionally, climate change plays an important role in determining the characteristics of individual species and thus on the ecosystems they inhabit. We set out to understand the responses of A. ovulum to habitat variables and to make projections based on the climate change scenarios described in the IPCC’s SSP1-2.6 and SSP5-8.5 criteria. We carried out seasonal bottom trawling surveys in the East China Sea region during 2018 and 2019 to fill this knowledge gap. Our results showed that the average individual size values ranged from 17.80−43.00 g·ind -1 in spring and 23.49−33.00 g·ind -1 in summer; the measured sea bottom temperature, sea bottom salinity, and depth value ranges were 10.81−27.06°C, 31.73–35.25‰, and 91–103 m independently in spring to winter. Our study showed that A. ovulum was distributed in the area between 27°–29°N, 122.5°–125°E during spring to autumn, and expanded into the area between 26.5°–32.5°N, 121°–124.5°E in winter. The core habitat of A. ovulum was centered on the area between 27.5°–28°N, 122.5°–123.5°E, and can be expected to expand to the northeast and southwest independently under the most likely global warming scenarios. Our results will benefit the development of suitable conservation measures for cephalopod habitats, and incorporate the impacts of climate change into fisheries management programs.

Improving forest gross primary productivity estimation through climate and trait integration - Hongge Ren; Li Zhang; Min Yan; Bo Zhang; Linlin Ruan (Ecological Modelling, 2025)

Compound heterozygous mutation of AFG3L2 causes autosomal recessive spinocerebellar ataxia through mitochondrial impairment and MICU1 mediated Ca2+ overload - Hongyu Li; Qingwen Ma; Yan Xue; Linlin Cai; Liwen Bao; Lei Hong; Yitao Zeng; Shu-Zhen Huang; Richard H. Finnell; Fanyi Zeng (Science China Life Sciences, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

Enhanced dechlorination for multi-source solid wastes using gas-pressurized torrefaction and its removal mechanism - Jia Fu; Linlin Yi; Kaiyuan Li; Yan Zhang; Tong Zhang; Aijun Li; Tianrun Wang; Yanyan Zou; Xian Li; Hong Yao (Chemical Engineering Journal, 2025)

Improving soil structure and function for continuous cropping of sweet melon using microalgae-based biological fertilizer - Linlin Yang; Xiaotong Song; Yanzhang Feng; Xiaoting Qiu; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Algal Research, 2025)

Total water level prediction at continental scale: Coastal ocean - Linlin Cui; Fei Ye; Y. Joseph Zhang; Haocheng Yu; Zhengui Wang; Saeed Moghimi; Gregory Seroka; Jack Riley; Shachak Pe'eri; Soroosh Mani; Edward Myers; Kyungmin Park; et al. (Ocean Modelling, 2024)

Low level exposure to BDE-47 facilitates the development of prostate cancer through TOP2A/LDHA/lactylation positive feedback circuit - Linlin Tian; Nan Zhou; Ning Zhao; Mengkai Qiao; Min He; Ziqing Mao; Wenjiong Xu; Dandan Xu; Yan Wang; Yan Xu; Tong Chen (Environmental Research, 2024)

Constructing multi-functional carbon-based aerogels for highly efficient photo-thermal desalination and water purification - Yuqian He; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Enrico Drioli; Jun Ma; Xi Quan Cheng (Desalination, 2024)

A multiscale dilated attention network for hyperspectral image classification - Chao Tu; Wanjun Liu; Wentao Jiang; Linlin Zhao; Tinghao Yan (Advances in Space Research, 2024)

Genes and Pathways Underpinning Klinefelter Syndrome at Bulk and Single-Cell Levels - Linlin Tian; Yan Yu; Ziqing Mao; Dandan Xu; Hongbo Zhang; Mengkai Qiao; Tong Chen; Wen Liu (Biochemical Genetics, 2024)

ChatEV: Predicting electric vehicle charging demand as natural language processing - Haohao Qu; Han Li; Linlin You; Rui Zhu; Jinyue Yan; Paolo Santi; Carlo Ratti; Chau Yuen (Transportation Research Part D: Transport and Environment, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Exosomal miR-129-2-3p promotes airway epithelial barrier disruption in PM2.5-aggravated asthma - Caihong Wang; Zeyu Niu; Yan Zhang; Nannan Liu; Xiaotong Ji; Jiayu Tian; Linlin Guan; Dongxing Shi; Huiqiu Zheng; Yuhui Gao; Lifang Zhao; Wenping Zhang; et al. (Journal of Environmental Management, 2024)

Characterization of low-molecular-weight fucoidan prepared by photocatalysis degradation and its regulation effect on metabolomics of LPS-stimulated macrophages - Lilong Wang; Linlin Wang; Jinhe Tian; Chunhong Yan; Chen Song; Shuangcai Xiao; Shuang Song (Food Bioscience, 2024)

Fabrication of polysaccharide-coated oleanolic acid-curcumin-coassembled nanoparticles (OA/Cur NPs): Enhancement of colloidal stability and water solubility - Linlin Yan; Han Liu; Yuhui Wang; Lulu Zhang; Chao Ma; A.M. Abd El-Aty (Food Chemistry, 2024)

Association between concentrations of rare earth elements in chorionic villus and risk for unexplained spontaneous abortion - Meng Lin; Lailai Yan; Xiaoye Wang; Yutong Wang; Ying Zhou; Linlin Wang; Chan Tian (Environmental Research, 2024)

Dietary Potassium and Magnesium Intake with Risk of Type 2 Diabetes Mellitus Among Rural China: the Henan Rural Cohort Study - Jia Li; Yuqian Li; Chongjian Wang; Zhenxing Mao; Tianyu Yang; Yan Li; Wenguo Xing; Zhuoyang Li; Jiaoyan Zhao; Linlin Li (Biological Trace Element Research, 2024)

A bibliometric analysis of blue carbon (1993–2023): evolution of research hot topics and trends - Shanshan Wang; Dandan Yan; Chenhao Wang; Linlin Wu; Yiming Huang (Frontiers in Marine Science, 2024)
Blue carbon refers to the carbon fixed in marine ecosystems such as mangroves, salt marshes, and seagrass beds. Considered a treasure house for capturing and storing carbon dioxide, it can alleviate environmental issues linked to climate change and positively influence the environments where people live. Thus, to clarify the hotspots and development trends of blue carbon research, bibliometric analysis incorporating ScientoPy and VOSviewer software were used to quantitatively analyze 4,604 blue carbon publications from Web of Science and Scopus databases between 1993 and 2023. The results indicate a rapidly growing number of published studies on blue carbon, with blue carbon research being multifaceted and gradually becoming an interdisciplinary and international topic. This study on blue carbon, which is based on keyword clustering analysis, comprises three stages. The analysis of the strength of the cooperative connections between scholars in various countries who have published work on blue carbon. found that the cooperation networks of developed countries are strong and those of developing countries are relatively weak. Quantitative trend analysis reveals a growing focus on the restoration and conservation of blue carbon ecosystems, with remote sensing being the predominant technology used in the blue carbon research field in recent years. In blue carbon research, increasing carbon sequestration capacity, climate change mitigation, and carbon sequestration in macroalgae remain potential hotspots for research and development.

PCDH11X mutation as a potential biomarker for immune checkpoint therapies in lung adenocarcinoma - Manjiao Liu; Meijia Yang; Bei Zhang; Sijian Xia; Jie Zhao; Linlin Yan; Yong Ren; Hao Guo; Jie Zhao (Journal of Molecular Medicine, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

Effect-directed analysis of androgenic compounds from sewage sludges in China - Tongtong Xiang; Chunzhen Shi; Yunhe Guo; Jie Zhang; Weicui Min; Jiazheng Sun; Jifu Liu; Xiliang Yan; Yanna Liu; Linlin Yao; Yuxiang Mao; Xiaoxi Yang; et al. (Water Research, 2024)

Wen-Yi and Chinese medicine: Why we need to pay attention? - Yibai Xiong; Linlin Bao; Yan Ma; Ling Zhang; Chuan Qin; Luqi Huang (Science Bulletin, 2024)

Energetics of eddy-mean flow interactions in the western tropical Pacific Ocean - Yuchao Hui; Linlin Zhang; Xiaomei Yan; Mengmeng Li; Fan Wang; Dunxin Hu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Measurement of Elastic Bi-modulus of Rock-type Materials: Insight from comparative and parallel tests - Yan Zhang; Hao Zheng; Huiling He; Peng Sha; Linlin Wang; Shengwen Qi; Xiaolin Huang; Jianhong Ye (Bulletin of Engineering Geology and the Environment, 2024)

Construction of Ni3S4@ZIS@C3N5 photocatalyst with type II and Z-type heterojunctions by self-assembly for efficient photocatalytic hydrogen evolution - Huixiang Yan; Wei Li; Huixing Yang; Yongzhuo Yu; Chaoyu Lv; Linlin Hou; Wenxu Zhang; Di Lin; Shichao Jiao (Environmental Research, 2024)

Nitrogen isotopic characteristics of aerosol ammonium in a Chinese megacity indicate the reduction from vehicle emissions during the lockdown period - Zhengjie Li; Hongwei Xiao; Wendell W. Walters; Meredith G. Hastings; Juan Min; Linlin Song; Weizhi Lu; Libin Wu; Wende Yan; Shuguang Liu; Yunting Fang (Science of The Total Environment, 2024)

Machine learning reveals the selection pressure exerted by nonantibiotic pharmaceuticals at environmentally relevant concentrations on antibiotic resistance genotypes - Shaojing Sun; Yan Sun; Jialu Geng; Linlin Geng; Fan Meng; Qing Wang; Hong Qi (Journal of Environmental Management, 2024)

Coagulation-centered three-step approach for removing by-product organic pollutants from tetrabromobisphenol A industrial wastewater: Experimental and theoretic investigations - Linlin Hao; Jingshuang Yan; Mingxuan Li; WeiMin Shao; Ming Zeng (Environmental Research, 2024)

Changes of microbial residues over century-long soil development after tidal flat reclamation in eastern China - Dezhi Yan; Weiyue Sun; Linlin Ye; Bo Liu (CATENA, 2024)

Quantitative distribution and quantized ecological threat of microplastics in farmland: Shanghai as an example - Zhengwen Li; Zhaofeng Song; Linlin Qiu; Yan Cao; Hairong Gu; Zhenqi Wang; Xiang Liu; Xiaoyong Qian (Journal of Hazardous Materials, 2024)

Microbiological hazards in infant and toddler food in China: A comprehensive study between 2004 and 2022 - Lin Teng; Linlin Huang; Haiyang Zhou; Baikui Wang; Min Yue; Yan Li (Food Research International, 2024)

UV-B application during the aeration process improves the aroma characteristics of oolong tea - Xiaohui Wang; Jingjie Cao; Xin Cheng; Xuyang Liu; Wenfeng Zhu; Yan Li; Xiaochun Wan; Shengkeng Chen; Linlin Liu (Food Chemistry, 2024)

An urban metabolism framework purpose to assess the dynamics of linear alkylbenzenes (LABs) discharge flows and driving forces at the city level in Guangdong province, China - Zihao Wu; Linlin Xia; Junye Zhong; Yan Zhang (Environmental Pollution, 2024)

Integrating photovoltaic noise barriers and electric vehicle charging stations for sustainable city transportation - Kai Zhang; Min Chen; Rui Zhu; Fan Zhang; Teng Zhong; Jian Lin; Linlin You; Guonian Lü; Jinyue Yan (Sustainable Cities and Society, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

Controllable synthesis of polyaspartic acid: Studying into the chain length effect for calcium scale inhibition - Meng-Long Zhang; Zheng Ruan; Yu Han; Zhi-Wei Cao; Linlin Zhao; Yuan-Qing Xu; Zhong-Yan Cao; Wen-Yan Shi; Ying Xu (Desalination, 2024)

2-Methoxyestradiol ameliorates paraquat-induced pulmonary fibrosis by inhibiting the TGF-β1/Smad2/3 signaling pathway - Linlin Hou; Fang Yang; Yan Zhang; Yi Li; Hongyi Yan; Cuicui Meng; Yuqi Du; Huanzhou Zhu; Ding Yuan; Yanxia Gao (Pesticide Biochemistry and Physiology, 2023)

Integrated analyses delineate distinctive immunological pathways and diagnostic signatures for Behcet’s disease by leveraging gene microarray data - Haoting Zhan; Linlin Cheng; Haolong Li; Yongmei Liu; Yuan Huang; Xiaomeng Li; Songxin Yan; Yongzhe Li (Immunologic Research, 2023)

Prognostic value of the WT-1 gene combined with recurrent cytogenetic genes in acute myeloid leukemia - Qing Zhang; Linlin Liu; Haotian Yan; Xiyang Ren; Mei Zhou; Shudao Xiong; Huiping Wang; Qianshan Tao; Zhimin Zhai (Immunogenetics, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Strategies for mapping protein hydrolysate profiles and pharmacokinetics based on non-targeted proteomics combining skyline-aided quantitative techniques - Shuying Mao; Wei Jin; Sisi Fu; Keanqi Liu; Feng Xu; Linlin Wu; Yexin Xu; Huizhu Yang; Huafang Liu; Guangji Wang; Yan Liang (Analytica Chimica Acta, 2023)

Estimation of urban-scale photovoltaic potential: A deep learning-based approach for constructing three-dimensional building models from optical remote sensing imagery - Longxu Yan; Rui Zhu; Mei-Po Kwan; Wei Luo; De Wang; Shangwu Zhang; Man Sing Wong; Linlin You; Bisheng Yang; Biyu Chen; Ling Feng (Sustainable Cities and Society, 2023)

Defensive Specialized Metabolites from the Latex of Euphorbia jolkinii - Shihong Luo; Chunshuai Huang; Juan Hua; Shuxi Jing; Linlin Teng; Ting Tang; Yan Liu; Shenghong Li (Journal of Chemical Ecology, 2023)

Dual-response near-infrared fluorescent probe for detecting cyanide and mitochondrial viscosity and its application in bioimaging - Wei Pan; Linlin Han; Xiaoqun Cao; Shili Shen; Xianhong Pang; Yan Zhu (Food Chemistry, 2023)

Nanophytoplankton and microphytoplankton in the western tropical Pacific Ocean: its community structure, cell size and carbon biomass - Wenzhuo Yan; Zhuo Chen; Linlin Zhang; Feng Wang; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2023)
Phytoplankton, as a crucial component of the marine ecosystem, plays a fundamental role in global biogeochemical cycles. This study investigated the composition and distribution of phytoplankton in the western Tropical Pacific Ocean using the Utermöhl method and carbon volume conversion. We identified four primary groups of phytoplankton: dinoflagellates (181 species), diatoms (73 species), cyanobacteria (4 species), and chrysophyceae (2 species). The clustering analysis classified phytoplankton into four groups based on their composition, which were found to be closely related to ocean currents. Diatoms were highly abundant in areas influenced by current-seamount interaction. In contrast, areas with little influence from ocean currents were dominated by Trichodesmium . The majority of phytoplankton had an equivalent spherical diameter (ESD) of 2-12 μm, with a few exceeding 25 μm. Although nanophytoplankton (ESD = 2-20 µm) dominated cell abundance, microphytoplankton (ESD = 20-200 µm) contributed significantly to carbon biomass (792.295 mg m -3 ). This study yielded valuable insights into the distribution and composition of phytoplankton in the western tropical Pacific Ocean, shedding light on the relationship between species distribution and ocean currents. In addition, it provided fundamental information regarding cell size and carbon biomass within the region.

Spatial distribution patterns across multiple microbial taxonomic groups - Xiongfeng Du; Songsong Gu; Zheng Zhang; Shuzhen Li; Yuqi Zhou; Zhaojing Zhang; Qi Zhang; Linlin Wang; Zhicheng Ju; Chengliang Yan; Tong Li; Danrui Wang; et al. (Environmental Research, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Relationships between denitrification rates and functional gene abundance in a wetland: The roles of single- and multiple-species plant communities - Yushuang Kong; Haikuo Zhang; Linlin Tian; Junji Yuan; Youchao Chen; Yan Li; Jian Chen; Scott X. Chang; Yunying Fang; Ehsan Tavakkoli; Yanjiang Cai (Science of The Total Environment, 2023)

Global, regional, and national deaths, disability-adjusted life years, years lived with disability, and years of life lost for the global disease burden attributable to second-hand smoke, 1990–2019: A systematic analysis for the Global Burden of Disease Study - Chunxia Zhai; Dingtao Hu; Guanghui Yu; Wanqin Hu; Qiqun Zong; Ziye Yan; Yuhua Wang; Linlin Wang; Tingyu Zhang; Hongyu Sun; Ling Cai; Liangyu Cui; et al. (Science of The Total Environment, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Impact of diurnal temperature range on other infectious diarrhea in Tongcheng, China, 2010–2019: a distributed lag non-linear analysis - Linlin Wang; Jian Cheng; Guanghui Yu; Qiqun Zong; Chunxia Zhai; Wanqin Hu; Yuhua Wang; Ziye Yan; Tingyu Zhang; Junwu Wang; Chengye Zhang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

Geochronology and geochemistry of the Late Triassic intrusive rocks in the Liaodong Peninsula, NE China: Petrogenesis and implications for early Mesozoic tectonic evolution - Peng Zhang; Yan Zhao; Linlin Kou; Deming Sha (International Geology Review, 2023)

Genesis of the Xinfang gold deposit, Liaodong Peninsula: Constraints from fluid inclusions, H-O-S-Pb isotopes, pyrite trace element concentrations, and chronology - Peng Zhang; Yan Zhao; Linlin Kou; Hong zhi Yang (Gondwana Research, 2023)

Alteration of alpha and beta diversity in nekton community by extreme marine heatwave events: An example from the East China Sea - Zunlei Liu; Linlin Yang; Liping Yan; Hui Zhang; Yi Zhang; Min Xu; Yan Jin; Jiahua Cheng (Frontiers in Marine Science, 2022)
In the year of 2016 to 2017, record-breaking marine heatwave (MHW) events occurred along the Chinese coast, exerting severe impacts on coastal fishes and fisheries. However, the response of the nekton community to MHW events still remains poorly understanding. Thus, to investigate the influences of the MHW events on species composition dynamics, this study conducted a survey on nekton communities in the northern East China Sea in the summers during 2014 to 2017. The recently-developed “heatwaveR” package was adopted to describe the variation characteristics of heatwaves within the study area, based on high-resolution remote-sensing sea surface temperature products. We also compared variations in the community structures of different biological groups before (2014–2015) and during the occurrence of the MHW events (2016–2017). During the MHW events, temperature increased by approximately 2.3°C in both 2016 and 2017. Compared with those before the MHW events, the biomass and dominance of several important crustaceans decreased, and the biomass of warm water affinity species increased significantly, while their richness and diversity decreased; the biomass of warm temperature affinity species declined significantly, while their diversity increased slightly. These results show the difference in the response rates of species with different thermal preferences and different species compositions to the extreme climate change. Beta diversity analysis revealed that the inter-group variation before and during the MHW event exceeded the intra-group variation, proving that MHWs changed the community structure to a certain extent. PERMANOVA test showed that the species compositions of planktivorous fish (FG1) and small-omnivorous fish (FG2) in the feeding-functional groups were significantly different before and during the MHW event, which may be attributed to the impact of MHWs on oligotrophic fishes through thermal preference and the trophic cascade effect. There was no significant change in the species compositions of other functional groups, indicating that medium-trophic and eutrophic fishes possessed certain adaptability to MHWs. Regarding fisheries management under extreme warming events, it would be advisable to diagnose temperature anomalies in the early stage, monitor changes in species abundance in the early life cycle, and then rapidly develop suitable fishing strategies.

LaeA regulates morphological development and ochratoxin A biosynthesis in Aspergillus niger - Mengwei Zhang; Yan Yang; Linlin Li; Shuwen Liu; Xianli Xue; Qiang Gao; Depei Wang; Ying Zhang; Jian Zhang (Mycotoxin Research, 2022)

Surveillance of long-term environmental elements and PM2.5 health risk assessment in Yangtze River Delta, China, from 2016 to 2020 - Keqin Wu; Yuanhua Meng; Yan Gong; Xuhui Zhang; Linlin Wu; Xinliang Ding; Xiaofeng Chen (Environmental Science and Pollution Research, 2022)

Incorporating egg-transporting pathways into conservation plans of spawning areas: An example of small yellow croaker (Larimichthys polyactis) in the East China Sea zone - Zunlei Liu; Yan Jin; Linlin Yang; Liping Yan; Yi Zhang; Min Xu; Jianhua Tang; Yongdong Zhou; Fen Hu; Jiahua Cheng (Frontiers in Marine Science, 2022)
Backward-in-time Lagrangian model can identify potential spawning areas by reconstructing egg drift trajectories, contributing to accurately designing potential priority conservation plans for spawning areas. In this study, we apply this approach to investigate the small yellow croaker ( Larimichthys polyactis ) with commercial value in China. A two-step spatial random forest (RF) model is used to predict the occurrence probability and abundance of their eggs and describe the optimal ecological range of environmental factors. A priority protection index (BPPI) of the spawning areas is established by combining the sites with the optimal occurrence and abundance and integrating backward tracking pathways. The result indicates that the model with 1-2 day time lags of environmental variables shows the optimum explanatory power. Temperature and salinity are the most important factors affecting oogenesis and show a regime shift in the response curve. They reflect the physiological regulation of parental sexual maturation by the environment. In addition, egg abundance correlates more strongly with chlorophyll-a (Chl a) concentration and depth, suggesting that parents prefer environments with shallow water and high prey density for spawning activities. The egg retrieval shows that the potential spawning sources are distributed near the southeastern part of the oogenesis site, with a maximum egg dispersal distance of no more than 30 km. This finding confirms that the coastal regions of Jiangsu Province are an important spawning ground for the small yellow croaker, making a significant contribution to the productivity and resilience of the fish.

The near-inertial waves observed east of the Philippines - Shengming Yuan; Xiaomei Yan; Linlin Zhang; Bing Yang; Chongguang Pang; Dunxin Hu (Journal of Oceanology and Limnology, 2022)

Radioactivity of Strontium-90 in Soil Samples Along the Hai River in Tianjin, China - Fei Chen; Linlin Yan; Qiang Xiong; Xiao Ge; Jing Liang; Zhen Zhang; Shengyuan Yang; Ling Jiao (Water, Air, & Soil Pollution, 2022)

Lower activity time constraint on the ore-controlling Erdaogou fault in the Qingchengzi orefield of the Liaodong Peninsula, NE China - Yan Zhao; Yuewen Feng; Peng Zhang; Linlin Kou; Zhongzhu Yang; Shenghui Li; Wei Wang (Acta Geochimica, 2022)

Drinking water elements constituent profiles and health risk assessment in Wuxi, China - Keqin Wu; Yuanhua Meng; Yan Gong; Linlin Wu; Wenwei Liu; Xinliang Ding (Environmental Monitoring and Assessment, 2022)

QpefBD: A Benchmark Dataset Applied to Machine Learning for Minute-Scale Quantitative Precipitation Estimation and Forecasting - Anyuan Xiong; Na Liu; Yujia Liu; Shulin Zhi; Linlin Wu; Yongjian Xin; Yan Shi; Yunjian Zhan (Journal of Meteorological Research, 2022)

Identifying Priority Conservation Areas of Largehead Hairtail (Trichiurus japonicus) Nursery Grounds in the East China Sea - Zunlei Liu; Yan Jin; Liping Yan; Yi Zhang; Hui Zhang; Chuyi Shen; Linlin Yang; Jiahua Cheng (Frontiers in Marine Science, 2022)
Identifying the spatio-temporal distribution hotspots of fishes and allocating priority conservation areas could facilitate the spatial planning and efficient management. As a flagship commercial fishery species, Largehead hairtail ( Trichiurus japonicus ) has been over-exploited since the early 2000s. Therefore, the spatio-temporal management of largehead hairtail nursery grounds could effective help its recovery. This study aims to predict juvenile largehead hairtail distribution patterns and identify priority conservation areas for nursery grounds. A two-stage hierarchical Bayesian spatio-temporal model was applied on independent scientific survey data (Catch per unit effort, CPUE) and geographic/physical variables (Depth, Distance to the coast, Sea bottom temperature, Dissolved oxygen concentration and Net primary production) to analyze the probability of occurrence and abundance distribution of juvenile largehead hairtail. We assessed the importance of each variable for explaining the occurrence and abundance. Using persistence index, we measured the robustness of hotspots and identified persistent hotspots for priority conservation areas. Selected models showed good predictive capacity on occurrence probability (AUC = 0.81) and abundance distribution ( r = 0.89) of juvenile largehead hairtail. Dissolved oxygen, net primary production, and sea bottom temperature significantly affected the probability of occurrence, while distance to the coast also affected the abundance distribution. Three stable nursery grounds were identified in Zhejiang inshore waters, the largest one was located on the east margin of the East China Sea hairtail national aquatic germplasm resources conservation zones (TCZ), suggesting that the core area of nursery grounds occurs outside the protected areas. Therefore, recognition of these sites and their associated geographic/oceanic attributes provides clear targets for optimizing largehead hairtail conservation efforts in the East China Sea. We suggested that the eastern and southern areas of TCZ should be included in conservation planning for an effective management within a network of marine protected areas.

Effects of Smooth Cordgrass Spartina alterniflora Invasion on Macrobenthic Fauna in the Yellow River Delta - Shaoyu Jiang; Chuanxin Zhang; Linlin Chen; Chunyun Liu; Lang Yan; Baoquan Li (Wetlands, 2022)

Climate change impacts on China’s marine ecosystems - Bin Kang; Gretta T. Pecl; Longshan Lin; Peng Sun; Peidong Zhang; Yuan Li; Linlin Zhao; Xin Peng; Yunrong Yan; Chunyan Shen; Wentao Niu (Reviews in Fish Biology and Fisheries, 2021)

DNA Methylation Analysis of the NR3C1 Gene in Patients with Schizophrenia - Linlin Liu; Jian Wu; Lili Qing; Jiajue Li; Hao Yang; Aicen Ji; Ming Yan; Liping Hu; Shengjie Nie (Journal of Molecular Neuroscience, 2020)

Multi‐century drought variability in the southern Min Mountains - Xiaoya Yan; Yang Deng; Haowen Fan; Jiajia Su; Linlin Gao; Xiaohua Gou (International Journal of Climatology, 2020)
Information on moisture variability is important for climate adaptation and planning, which is urgently needed for the Jiuzhaigou County after it was hit by a magnitude 7.0 earthquake in August 2017, resulting in potential interactions between the earth surface processes and the hydroclimate. To study the regional hydroclimatic history beyond instrumental records, the first tree‐ring hydroclimate reconstruction, based on Pinus tabuliformis , was conducted in the southern Min Mountains, which is situated close to the areas affected by the Jiuzhaigou earthquake. The reconstruction, spanning from 1684 to 2017, explained 59% of the variance for May–August standardized precipitation evapotranspiration index at a 12‐month scale during 1962–2017. The recent drought, which occurred from 1992 to 2017 was the longest in duration, largest in magnitude, and had the second highest intensity. The most severe single year drought occurred in 1824, which was lower than the long‐term mean by 4 σ and affected several regions in and around the Northeast Qinghai‐Tibet Plateau. The drought reconstruction was consistent with other moisture reconstructions, but dissimilar were also exist during some periods. There was a significant correlation between drought reconstruction and sea surface temperature over many oceans. However, the correlations were unstable over time. This study suggests the importance of developing a density tree‐ring network to identify the spatial and temporal drought variability, as well as long‐term record for understanding regional climate dynamics.

NLRP3 Deficiency Attenuates Secondary Degeneration of Visual Cortical Neurons Following Optic Nerve Injury - Zhou Zhang; Wenyi Liu; Yubin Huang; Linlin Luo; Xiaofeng Cai; Yunjia Liu; Liqianyu Ai; Jun Yan; Sen Lin; Jian Ye (Neuroscience Bulletin, 2020)

Sulfate-enhanced degradation of Rhodamine B in the hydrogen peroxide/hydroxylamine system - Shengli Wang; Linlin Yan; Xiaohui Guan; Yanping Jia; Lianfa Song; Haifeng Zhang (Environmental Chemistry Letters, 2019)

Exploration of the key functional strains from an azo dye degradation microbial community by DGGE and high-throughput sequencing technology - Yan Chen; Lizhen Zhang; Linlin Feng; Guotao Chen; Yuanxiu Wang; Zhijun Zhai; Qinghua Zhang (Environmental Science and Pollution Research, 2019)

Luteolin decreases the yield of influenza A virus in vitro by interfering with the coat protein I complex expression - Haiyan Yan; Linlin Ma; Huiqiang Wang; Shuo Wu; Hua Huang; Zhengyi Gu; Jiandong Jiang; Yuhuan Li (Journal of Natural Medicines, 2019)

Major ion and dissolved heavy metal geochemistry, distribution, and relationship in the overlying water of Dongting Lake, China - Yan Chen; Lingqing Wang; Tao Liang; Jun Xiao; Jing Li; Haicheng Wei; Linlin Dong (Environmental Geochemistry and Health, 2019)

Carbon, nitrogen and phosphorus stocks differ among vegetation patch types in a degraded alpine steppe - Yan Yan; Linlin Tian; Ziyin Du; Scott X. Chang; Yanjiang Cai (Journal of Soils and Sediments, 2019)

A novel long non-coding RNA, lncKBTBD10, involved in bovine skeletal muscle myogenesis - Mingming Chen; Xin Li; Xiaojuan Zhang; Yan Li; Junxing Zhang; Minhui Liu; Linlin Zhang; Xiangbin Ding; Xinfeng Liu; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Contribution of heterotrophic bacterioplankton to cyanobacterial bloom formation in a tributary backwater area of the Three Gorges Reservoir, China - Lunhui Lu; Linlin Xu; Jixiang Yang; Zhe Li; Jinsong Guo; Yan Xiao; Juanjuan Yao (Environmental Science and Pollution Research, 2018)

Analyzing Coastal Wetland Degradation and its Key Restoration Technologies in the Coastal Area of Jiangsu, China - Linlin Cui; Guosheng Li; Ninglei Ouyang; Fengyun Mu; Fu Yan; Youtian Zhang; Xiaoyang Huang (Wetlands, 2018)

Synaptobrevin-2 facilitates the trafficking and function of atrial SK2 channel - Tao Li; Xuehui Fan; Yiyan Yu; Linlin Chen; Wenjun Huang; Yan Yang; Jimin Cao; Xiaorong Zeng; Xiaoqiu Tan (Science China Life Sciences, 2018)

Plantactinospora solaniradicis sp. nov., a novel actinomycete isolated from the root of a tomato plant (Solanum lycopersicum L.) - Wenchao Li; Xiaowei Guo; Linlin Shi; Junwei Zhao; Liangliang Yan; Xiaotong Zhong; Chen Zhang; Yufei Chen; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

MicroRNA-192 regulates hypertrophic scar fibrosis by targeting SIP1 - Yan Li; Julei Zhang; Wei Zhang; Yang Liu; Yuehua Li; Kejia Wang; Yijie Zhang; Chen Yang; Xiaoqiang Li; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

Variability of Antarctic Intermediate Water south of Australia and its relationship with frontal waves - LinLin Zhang; XiaoMei Yan; Che Sun; DunXin Hu (Science China Earth Sciences, 2016)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

Biosorption and degradation of decabromodiphenyl ether by Brevibacillus brevis and the influence of decabromodiphenyl ether on cellular metabolic responses - Linlin Wang; Litao Tang; Ran Wang; Xiaoya Wang; Jinshao Ye; Yan Long (Environmental Science and Pollution Research, 2016)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

Event-related potentials elicited by social commerce and electronic-commerce reviews - Yan Bai; Zhong Yao; Fengyu Cong; Linlin Zhang (Cognitive Neurodynamics, 2015)

MRP1 knockdown down-regulates the deposition of collagen and leads to a reduced hypertrophic scar fibrosis - Yan Li; Longlong Yang; Zhao Zheng; Jihong Shi; Xue Wu; Hao Guan; Yanhui Jia; Ke Tao; Hongtao Wang; Shichao Han; Jianxin Gao; Bin Zhao; et al. (Journal of Molecular Histology, 2015)

Analysis of the temporal and spatial distribution of water quality in China’s major river basins, and trends between 2005 and 2010 - Jinjian Li; Xiaojie Meng; Yan Zhang; Juan Li; Linlin Xia; Hongmei Zheng (Frontiers of Earth Science, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Effect of mechanical stretch on the expressions of elastin, LOX and Fibulin-5 in rat BMSCs with ligament fibroblasts co-culture - Zhao Bing; Liang Linlin; Yan Jianguo; Ren Shenshen; Ren Ruifang; Zhang Xi (Molecular Biology Reports, 2012)

Lipopolysaccharide induces expression of SSeCKS in rat lung microvascular endothelial cell - Chun Cheng; Haiou Liu; Haiyan Ge; Ji Qian; Jing Qin; Linlin Sun; Menling Chen; Meijuan Yan; Aiguo Shen (Molecular and Cellular Biochemistry, 2007)

Inhibitory connections among rostral medullary expiratory neurones detected with cross-correlation in the decerebrate rat* - Linlin Shen; Yan-Mei Li; James Duffin (Pflügers Archiv - European Journal of Physiology, 2003)